Insights into insecticide-resistance mechanisms in invasive species: Challenges and control strategies - Siddiqui, Junaid Ali; Fan, Ruidong; Naz, Hira; Bamisile, Bamisope Steve; Hafeez, Muhammad; Ghani, Muhammad Imran; Wei, Yiming; Xu, Yijuan; Chen, Xiaoyulong (Frontiers in Physiology, 2023)
Threatening the global community is a wide variety of potential bioweapons, most notably invasive pest species. Invasive pest species are non-native organisms that humans have either accidentally or intentionally spread to new regions. One of the most effective and first lines of control strategies for controlling pests is the application of insecticides. These toxic chemicals are employed to get rid of pests, but they pose great risks to people, animals, and plants. Pesticides are heavily used in managing invasive pests in the current era. Due to the overuse of synthetic chemicals, numerous invasive species have already developed resistance. The resistance development is the main reason for the failure to manage the invasive species. Developing pesticide resistance management techniques necessitates a thorough understanding of the mechanisms through which insects acquire insecticide resistance. Insects use a variety of behavioral, biochemical, physiological, genetic, and metabolic methods to deal with toxic chemicals, which can lead to resistance through continuous overexpression of detoxifying enzymes. An overabundance of enzymes causes metabolic and target site resistance, detoxifying pesticides and rendering them ineffective against pests. A key factor in the development of metabolic resistance is the amplification of certain metabolic enzymes, specifically esterase’s, Glutathione S-transferase, Cytochromes p450 monooxygenase, and hydrolyses. Additionally, insect guts offer unique habitats for microbial colonization, and gut bacteria may serve their hosts a variety of useful services. Detoxification of insecticides is one of them playing a key role in resistance development. The complete knowledge of invasive pest species and their mechanisms of resistance development could be very helpful in coping with the challenges and effectively developing strategies to control invasive species. IPM is particularly effective at lowering the risk of chemical, and environmental contaminants and the resulting health issues, and it may also offer the most effective ways to control insect pests.